Summa (Quaestiones ordinariae) art. LIII-LV - Henry, of Ghent, 1217?-1293 (Ancient and medieval philosophy., 2015)
Henry of Ghent's Summa, art. 53-55, was composed shortly after Christmas of 1281, at the height of Henry's teaching career in the Theology Faculty at the University in Paris. These questions, which begin the ‘second part' of his Summa, are devoted to the Persons of the Trinity. They contain Henry's philosophical analyses of the theoretical concepts person, relation, and universals. The text has been reconstructed based upon manuscripts copied from a first and second Parisian university exemplar. In the critical study that precedes the Latin text, the editors argue that the manuscript, Biblioteca VATICANA, Borghese 17, which contains the texts of these articles and which has, in the latter part of this manuscript, many of the features of an exemplar divided into pecia, could not have been the exemplar divided into pecia for these particular articles. The volume concludes with the typical tables.